METODE LATIHAN TERBIMBING SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS-KREATIF DALAM PEMBELAJARAN MENULIS CERPEN - HELGA SABRINA SIANTURI (Universitas Negeri Medan, 2012)
Abstract Writing is an activity that is not preferred by most students. There are many things of which lies behind this problem is the difficulty in determining the diction, it is difficult to determine the theme, it is difficult to find inspiration, hard to put the idea, and some students thought he was not talented. Short story elements that are considered to be a barrier for novice poets. Therefore, students should be able to boost the learning experience to enhance critical thinking skills are realized into the creative process. Efforts to do to minimize these barriers is to apply the method as an alternative guided exercises in learning to write short stories that are expected to increase the ability to think critically and creatively to help students in their ideas realized in the form of writing. Keyword: writing short stories, guided exercises, critical thinking, creative, learning to write short stories